2019
DOI: 10.3390/app9101967
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Removal of Cr(VI) by Lime Peel and Pineapple Core Wastes

Abstract: The search for efficient and environmentally friendly adsorbents has positioned lignocellulosic materials as attractive and low-cost alternatives instead of synthetic materials. Consequently, the present work investigates the efficacy of untreated lime peel (LM) and pineapple core (PP) as biosorbents for Cr(VI) removal. The maximum adsorption capacities (acquired at 24 h) of these sorbents were 9.20 and 4.99 mg/g, respectively. The use of these sorbents is expected to offer a rapid and efficient solution to tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…A compound such as chromium is carcinogenic and mutagenic when released into the environment. In order to remove chromium, the authors have reported that the effect of pH, bio-adsorbent dosage and temperature affected the dye sorption process, where the maximum adsorption capacities of pineapple possessed the highest value compared to lime [142]. Chromium removal by pineapple leaf fibre by polyethyleneimine-grafting had the highest adsorption capacity (222 mg/g) [143] compared to bio-adsorbent from date palm empty fruit bunch [144] and jackfruit peel [145] that reported lower chromium adsorption capacity of 70.49 mg/g and 13.50 mg/g, respectively.…”
Section: Bio-adsorbentmentioning
confidence: 99%
“…A compound such as chromium is carcinogenic and mutagenic when released into the environment. In order to remove chromium, the authors have reported that the effect of pH, bio-adsorbent dosage and temperature affected the dye sorption process, where the maximum adsorption capacities of pineapple possessed the highest value compared to lime [142]. Chromium removal by pineapple leaf fibre by polyethyleneimine-grafting had the highest adsorption capacity (222 mg/g) [143] compared to bio-adsorbent from date palm empty fruit bunch [144] and jackfruit peel [145] that reported lower chromium adsorption capacity of 70.49 mg/g and 13.50 mg/g, respectively.…”
Section: Bio-adsorbentmentioning
confidence: 99%
“…These functional groups present on their surfaces have charges that can facilitate binding of a particular pollutant by varying pH levels (Rastogi et al, 2019). Rosales et al (2019) investigated the role of untreated lime peel and pineapple core wastes in the removal of Cr (VI) from aqueous solutions with adsorption capacities of 9.20 and 4.99 mg/g respectively at pH 2.01. In an another recent study conducted using peels of Artocarpus nobilis for the removal of Ni(II) showed enhanced metal removal efficiency from 50 to 71 to 93% through optimization processes having 12,048 mg/kg as maximum adsorption capacity via static and dynamic conditions with Freundlich model as the best fitted adsorption model where regression coefficient has 0.994 value (Priyantha and Kotabewatta, 2019).…”
Section: Agricultural Solid Wastes As Adsorbents/ Nonconventional Grementioning
confidence: 99%
“…Usually, Cr(VI) is found as chromate ions (CrO4 2-) or dichromate (Cr2O7 2 ), which enter easily in contact with biologic barriers, presenting carcinogenic and mutagenic behaviors, besides, Cr(VI) is 500 more times toxic and moves better than Cr(III) [5,6]. Although Cr(III) is not toxic, when is encountered in aqueous solutions may become toxic by oxi-reduction to Cr(VI) [7].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, biosorption is an alternative against the elimination of heavy metals from industrial effluents with the aim to achieve high removal percentages, since the adsorbents from agroindustrial wastes present excellent properties for maintenance, low cost, easy processing, good reusability and wide availability [2,9]. Among the materials widely studied with excellent results for the removal of Cr(VI) in aqueous solutions, are found: peels of lime [7], rice and lychees [4,5], orange [11], apple [12], nut [13,14], lemon [15] plantain [10,16], among others [3,17,18]. Hence, this study compares the Cr(VI) adsorption capacity using orange peels and corncob as bioadsorbents, performing a batch system.…”
Section: Introductionmentioning
confidence: 99%